MINARET: A Recommendation Framework for Scientific Reviewers - R. Moawad, Mohamed (2019)
We are witnessing a continuous growth in the size of scien tific communities and the number of scientific publications. This phenomenon requires a continuous effort for ensuring the quality of publications and a healthy scientific evalu ation process. Peer reviewing is the de facto mechanism to assess the quality of scientific work. For journal editors, managing an efficient and effective manuscript peer review process is not a straightforward task. In particular, a main component in the journal editors’ role is, for each submit ted manuscript, to ensure selecting adequate reviewers who need to be: 1) Matching on their research interests with the topic of the submission, 2) Fair in their evaluation of the submission, i.e., no conflict of interest with the authors, 3) Qualified in terms of various aspects including scientific impact, previous review/authorship experience for the jour nal, quality of the reviews, etc. Thus, manually selecting and assessing the adequate reviewers is becoming tedious and time consuming task. We demonstrate MINARET, a recommendation framework for selecting scientific reviewers. The framework facilitates the job of journal editors for conducting an efficient and effective scientific review process. The framework exploits the valuable information available on the modern scholarly Websites (e.g., Google Scholar, ACM DL, DBLP, Publons) for identifying candidate reviewers relevant to the topic of the manuscript, filtering them (e.g. excluding those with potential conflict of interest), and ranking them based on several metrics configured by the editor (user). The framework extracts the required information for the rec ommendation process from the online resources on-the-fly which ensures the output recommendations to be dynamic and based on up-to-date information.